2013
DOI: 10.1002/hep.26454
|View full text |Cite
|
Sign up to set email alerts
|

Primary sclerosing cholangitis, autoimmune hepatitis, and overlap in utah children: Epidemiology and natural history

Abstract: The epidemiology and natural history of pediatric primary sclerosing cholangitis (PSC), autoimmune sclerosing cholangitis (ASC), and autoimmune hepatitis (AIH) are not well characterized. Using multiple, overlapping search strategies followed by a detailed records review, we identified all cases of pediatric PSC, ASC, AIH, and inflammatory bowel disease (IBD) in a geographically isolated region of the United States. We identified 607 cases of IBD, 29 cases of PSC, 12 cases of ASC, and 44 cases of AIH. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
202
4
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(229 citation statements)
references
References 46 publications
16
202
4
7
Order By: Relevance
“…Previous reports of pediatric prevalence are scarce and vary from 2.2 in non-First Nation (indigenous native Canadian) communities to 9.9 in First Nation communities per 100 000 children in British Columbia. 28 A recent report by Deneau et al 13 in Utah described an incidence of 0.4 case per 100 000 children and a prevalence of 3 per 100 000. The previously reported incidence in adults ranged from 0.1 to 1.9 per 100 000 per year (including some adolescents).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports of pediatric prevalence are scarce and vary from 2.2 in non-First Nation (indigenous native Canadian) communities to 9.9 in First Nation communities per 100 000 children in British Columbia. 28 A recent report by Deneau et al 13 in Utah described an incidence of 0.4 case per 100 000 children and a prevalence of 3 per 100 000. The previously reported incidence in adults ranged from 0.1 to 1.9 per 100 000 per year (including some adolescents).…”
Section: Discussionmentioning
confidence: 99%
“…12 A recent study in pediatric patients reported an incidence of 0.4 case per 100 000 children. 13 Another study from Poland reported an incidence of 3 to 4 per 100 000 children. 14 Available adult data indicate an incidence varying from 0.67 to 2 cases per 100 000 people.…”
Section: What This Study Addsmentioning
confidence: 99%
“…AIH is a rare condition both in adults and children, with a reported incidence of 0.4 and 3.0/100,000 children [85,86].…”
Section: Autoimmune Hepatitis and Autoimmune Sclerosing Cholangitismentioning
confidence: 99%
“…Although there are still no recommendations for routine serological CD screening in patients with AIH, the association between these two diseases should be considered if one of them is diagnosed. Rare cases of CD associated with other autoimmune liver diseases such as primary sclerosing cholangitis (PSC) and "overlap" syndrome (AIH / PSC) were described in children [35,36].…”
Section: Celiac Disease and Autoimmune Hepatitismentioning
confidence: 99%